Short term production planning of open-pit coal mine based on UAV data - Ensan FU; Runcai BAI; Wenhui ZHANG; Jie YUAN (Meitan kexue jishu, 2024)
In order to improve the efficiency of making short-term (daily and weekly) production plan, fast analysis of the completion of equipment plan and the effect of visual design and visual expression, based on the UAV image data, the paper puts forward the method of making short-term production plan quickly, and develops the Intelligent Mining Design Software System by C + + language, “IMDS” software for short. The results show that: ① the visual effect of short-term planning is enhanced by using UAV image data; ② the Stope Step Line of opencast coal mine in the range of 1 500 m × 1 500 m is automatically generated by using UAV image data; The time is 17.392 s, but the manual drawing takes 5 min; ③ the weekly plan and daily plan are made by using software platform, which reduces the need of repeated on-site inspection by miners and the complexity of calculation of traditional mining entity and block, the internal pre-equipment capability analysis module directly analyzes the short-term plan of the completion of equipment information; ④ based on image data for ramp rapid rendering, automatic calculation of ramp fill and excavation volume, to achieve the accuracy of transport road construction; ⑤ “IMDS” software provides 10 functional modules, 235 sub-functions, the short-term planning of UAV image data and the rapid monthly and annual planning of engineering quantities and precise determination of engineering positions based on three-dimensional geological entity modules can be realized; ⑥ the short-term production plan can be released to the Integrated Management and control platform of opencast coal mine by the way of data release, which can realize the visual display of plan data, realize the data one by one, and ensure the accuracy and safety of data. The development of the system software contributes to the further development of the intelligent mining design software system.